Family Issues In Caring For Patients With Chronic Kidney Failure - Anisa Purnamasari; Nazaruddin Nazaruddin; Cece Indriani; Sari Arie Lestari; Zahalim; Wa Ode Nova Noviyanti (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: According to the World Health Organization (WHO) and the Global Burden of Disease (GBD) project, kidney diseases significantly contribute to the global disease burden, resulting in approximately 850,000 deaths annually and 15,010,167 cases of disability, which lead to a decline in quality of life. Chronic kidney disease (CKD) patients undergoing hemodialysis face various issues that can cause biological, psychological, social, and spiritual imbalances. Objectives: This study aims to explore the challenges families encounter when caring for patients with chronic kidney disease. Methods: Utilizing a qualitative phenomenological research approach, the study involved in-depth interviews with a sample of five validated participants. The research identified four themes: (1) loyalty in caring for CKD patients; (2) feelings of sadness and concern regarding the patient's condition; (3) emotional burden of caregiving; and (4) acceptance of the patient's condition, with a central theme of accepting the CKD patient's status. Results: The research findings revealed four themes based on data collected from participants 1 to 5: (1) commitment to caring for patients with Chronic Kidney Disease (CKD), (2) feelings of sadness and concern regarding the condition of CKD patients, (3) emotional burden associated with caring for CKD patients, and (4) acceptance of the CKD patients' condition. The data analysis process, based on the interview results from each participant, will be elaborated upon according to themes, sub-themes, and categories, along with excerpts from participants' statements. Conclusions: The findings from this study, which comprise four themes, indicate that families caring for patients with Chronic Kidney Disease (CKD) face various psychological challenges that, if not addressed with appropriate coping mechanisms, can adversely affect their mental health status.